1999
DOI: 10.1046/j.1365-2958.1999.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation and repression of photosynthesis gene transcription in Rhodobacter capsulatus

Abstract: SummaryIt has been known for over half a century that anoxygenic photosynthetic bacteria maximally synthesize their photosystems in the absence of oxygen. During the last decade, it has become clear that this regulation is largely at the transcriptional level, with photosynthesis genes expressed only under anaerobic conditions. We describe here in vitro reconstitution of activation and repression of three photosynthesis promoters, bch (bacteriochlorophyll biosynthesis), puc (light-harvesting II apoproteins) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…This is the first demonstration of activation by a wild-type regulator in this family since in a previous transcription analysis with R. capsulatus RegA the workers used a gain-of-function mutant with altered in vitro properties (RegA*) (5). In this regard, it is significant that more than 10-fold more R. capsulatus RegA* protein than wild-type PrrA was needed to activate expression from cycA P2 (27).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is the first demonstration of activation by a wild-type regulator in this family since in a previous transcription analysis with R. capsulatus RegA the workers used a gain-of-function mutant with altered in vitro properties (RegA*) (5). In this regard, it is significant that more than 10-fold more R. capsulatus RegA* protein than wild-type PrrA was needed to activate expression from cycA P2 (27).…”
Section: Discussionmentioning
confidence: 92%
“…In studies of response regulators that are closely related to PrrA, it has been shown that Bradyrhizobium japonicum RegR binds to the promoter region of the fixR-nifA operon (2,12) and Rhodobacter capsulatus RegA directly interacts with the promoters of more than 20 target genes (3,5,9,10,48,50). The apparent binding sites for these proteins at target promoters are located at different distances from their transcriptional start sites, making the mechanism of transcription activation an interesting question (3,5,11,48).…”
mentioning
confidence: 99%
“…PrrA, phosphorylation by PrrB; FnrL, reassembly of cofactor (Eraso & Kaplan, 1995;Zeilstra-Ryalls & Kaplan, 1998). Also, there was a report that RegA, a PrrA homologue in R. capsulatus, competed with CrtJ to bind to the bchC promoter region (Bowman et al, 1999). Therefore, it is proposed that an anaerobic activator regulates photosystem gene expression under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids pRGK301, pHTT7f1-NH␣, pMKSe2, and pT7␤Ј were described previously (3,4,25,27,30). pRGK325, which allows overexpression of the R. capsulatus ␣ subunit of RNAP, was made by PCR of the rpoA gene from the chromosome of R. capsulatus SB1003 by use of the upstream oligonucleotide 5Ј-GAGGCAGAGCATATGATCCACAAGA ATTGG-3Ј and the downstream oligonucleotide 5Ј-CGGGATCCTCAGAACT GGTCTTCGAAGCGCTTGGCC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Kranz et al previously noted that R. capsulatus and other ␣-proteobacteria (see reference 15 for a review) may have Ϫ10 features different from those of organisms with a lower GϩC content (3,4). For another ␣-proteobacterium, Sinorhizobium meliloti, most of the 70 promoters that have been characterized are not transcribed by the E. coli RNAP in vivo or in vitro, but the S. meliloti RNAP can initiate transcription at typical E. coli 70 promoters (23).…”
mentioning
confidence: 99%